Karakteristik Sensoris dan Kimia Selai Mangga Lalijiwa (Mangifera indica) Dengan Menggunakan Pemanis Stevia (Stevia rebaudiana) Rendah Kalori - Meylia Aisyah Putri; Khusnul Khotimah; Lativa Lisya Maghfira; Anis Asmediana (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
Mango jam is made by adding sugar into mango which play a role as sweetener and thickener of the jam. Sugar contains high calorie which not beneficial for a people with diabetics. However, stevia is used as an alternative to replace sugar which expected to have lower calories, so the jam is safe to be consumed including for diabetics. The aim of this study was to determine the optimum concentration of stevia sweetener in lalijiwa mango jam especially in the sensory and chemical characteristics. The study used one factor complete randomized design with the comparison of mango and stevia of A1 (95%:5%), A2 (90%:10%), A3 (85%:15%), A4 (80%:20%) with a total amount of 250 gr. The results showed that from the overall parameters, sample A1 was the most preferred. While the chemical composition showed that the moisture, vitamin c, total dissolved solid, and total calories was 38,44%; 8,376 mg/100gr; 25 (°Brix); 905,941 cal/g; respectively.